Between sociology and aestheticism – yet another attempt to bridge over troubled water - Edström, Olle (Danish Yearbook of Musicology, 2006)
The sociologist Peter Martin and music historian Bo Marschner have recently criticized the modus operandi of the Gothenburg School of Musicology. The former alleges underprivileging sociological aspects in our studies while the latter suggests neglect of the musical work itself. My critique of these issues is prefaced by my argument that there is much to be learned from research in linguistics and psychology that deals with ‘pre-social’ and ‘biological’ prerequisites for music and culture. Then I discuss what is implied when Martin and other contemporary sociologists insist on the importance of the social as the focal point where all other factors – music among them – are brought together. I include in this part a discussion of the advantages of the concept ‘affordance’. With Keller’s theory of linguistic signs as a point of departure, I explore the ontological status of music and the possibilities of the use of music as a means of communication. I argue that music in our culture has a rhetorically intensifying, emotional and limited associative dimension. Further I consider Marschner’s epistemological outlook and views of music as an aesthetic experience, and his critique of my sociomusicological works. His views are supplemented with the views of a few other scholars. In a concluding discussion I attempt to bridge the gap between a sociological and an aesthetic understanding of music, as both lead to an incomplete understanding of the use of and meaning of music. I argue for an understanding of music from the viewpoints of a) situation/time for, b) place of, c) the structure of, and d) the performance of music. What is important to me is to understand why and how music was used and is used in what ways. It is from a contemporary reflexive position that I argue for an understanding of the ongoing social process.